Instalações sonoras contemporâneas: espaço e sensorialidade - Nunes, Cristiane dos Guimarães Alvim (2019)
Within contemporary artistic productions, Sound Art is the art that uses sound as a fundamental element. It has a varied repertoire, covering areas such as Architecture and Music, among others. This research is dedicated to the investigation of the specificities of this contemporary artistic production. The methodological path comprised, first, a theoretical investigation on the transformations of space issues in 20th Century Art. The research also involved a theoretical deepening on essential aspects of Sound Art; among them: spatiality, sensoriality, interactivity, sound, visuality. Based on these aspects, the work also included the analysis of the following sound installations: Lines (2016) by Anders Lind, Oasi (2014) by Licia Galizia and Michelangelo Lupone and 329 Prepared Dc-Motors, Cotton Balls, Toluene Tank (2013) by Zimoun. The analysis revealed the spatial character of the sound works that bring them closer to architecture. In addition, it highlighted the sensoriality that is strongly present in most sound productions. Some issues such as audience participation, visual aspect, the sound, among others, were also clear during the analysis. Finally, this research identified that Sound Art presents a rich and diverse repertoire, composed of sensitive and thought-provoking works, and stands out as a vast and valuable field to be explored.